2012
DOI: 10.5812/atr.5397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gabapentin on Morphine Consumption and Pain after Surgical Debridement of Burn Wounds: A Double-Blind Randomized Clinical Trial Study

Abstract: Background: Burn pain is recognized as being maximal during therapeutic procedures, and wound debridement can be more painful than the burn injury itself. Uncontrolled acute burn pain increases the stress response and the incidence of chronic pain and associated depression. Although opiates are excellent analgesics, they do not effectively prevent central sensitization to pain. The anticonvulsant gabapentin has been proven effective for treating neuropathic pain in large placebo-controlled clinical trials. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…As is often the case with the introduction of adjuvant drug treatment studies are difficult to compare due to the inherent variability of drug dosage, regimen, and use of adjuvant drugs and length of treatment. A similar study looking at the effects of gabapentin on morphine consumption in burns patients by Cuignet et al (2), although reaching the same overall conclusions as Rimaz et al (1) used a very different dosing regimen; a single dose of 1200mg gabapentin pre-operatively (1) and 2400mg daily from burn day 3-24 and results recorded for 21 days pre and post-surgical debridement (2) respectively. Additionally, in a further case series using gabapentin for acute burn pain Gray et al (3) used regimens as varied as 1000mg four times per day with concurrent oxycodone and 300mg three times per day are described.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…As is often the case with the introduction of adjuvant drug treatment studies are difficult to compare due to the inherent variability of drug dosage, regimen, and use of adjuvant drugs and length of treatment. A similar study looking at the effects of gabapentin on morphine consumption in burns patients by Cuignet et al (2), although reaching the same overall conclusions as Rimaz et al (1) used a very different dosing regimen; a single dose of 1200mg gabapentin pre-operatively (1) and 2400mg daily from burn day 3-24 and results recorded for 21 days pre and post-surgical debridement (2) respectively. Additionally, in a further case series using gabapentin for acute burn pain Gray et al (3) used regimens as varied as 1000mg four times per day with concurrent oxycodone and 300mg three times per day are described.…”
mentioning
confidence: 82%
“…I read with interest the study by Rimaz et al (1) which showed a statistically significant reduction in visual analogue pain scores and morphine consumption in a double blind randomised setting with 25 patients in each wing. This is not the first study to suggest that in tackling the complex mechanism of post-burn hypersensitivity, as yet not fully understood but thought to be similar to post-operative pain hypersensitivity; analgesics with different but synergistic effects may prove superior to opioid analgesia alone (2, 3).…”
mentioning
confidence: 99%
“…I read with great interest the recent manuscript by Siamak Rimaz on “ Effect of Gabapentin on Morphine Consumption and Pain after Surgical Debridement of Burn Wounds: A Double-Blind Randomized Clinical Trial Study” published in Archives of Trauma Research (1). In this article they recruited 50 patients and through a randomized, double-blind, placebo-controlled study demonstrated a significant improvement in pain scores and clinical parameters after administration of a single oral dose of 1200mg gabapentin.…”
Section: Dear Editormentioning
confidence: 99%
“…I read with great interest the contribution “Effect of Gabapentin on Morphine Consumption and Pain after Surgical Debridement of Burn Wounds: A Double-Blind Randomized Clinical Trial Study” by Raziet al (1). Carrying out a Randomized Controlled Trial without funding and especially in our region is an uphill task indeed.…”
mentioning
confidence: 99%